VARIABEL-VARIABEL YANG MEMPENGARUHI PRESTASI KERJA DI BIRO KEUANGAN SEKRETARIAT DAERAH PROVINSI KALIMANTAN TIMUR - Arief Rahman (Magister Administrasi Publik FISIP Universitas Mulawarman, 2017)
The purpose of this study is to determine the effect of environmental leadership and work together on work performanceof employees in the Finance Bureau of East Kalimantan Provincial Secretariat. Based on data analysis and hypothesis testing, it is found that the three variables, namely Leadership (X1), Work Environment (X2) and Job Performance(Y) has a positive influence and strong, this is evidenced by r=0.708 which provide guidelines for the interpretation put forward by Sugiyono which is in the interval from 0.60 to 0.799 were included in the strong category. From the research that has been conducted by the author, Factors Affecting Job Performance in the Financial Bureau of East Kalimantan Provincial Secretariat included in the category of strong, therefore the existing leadership style must be maintained so that employees who have a good performance can be maintained and enhanced.